A Review on Modern Lunar Crescent Visibility Criterion - Muhamad Syazwan Faiz; Mohd Nawawi, Mohd Saiful Anwar; Mohd Hafiz Mohd Saadon; Nazhatulshima Ahmad (Malaysian Journal of Science, 2025)
The modern lunar crescent visibility criterion is a criterion produced in the 20th century, which began with Fotheringham’s criterion in 1910 and continued until the present date. A limited number of research studies have been conducted on the modern lunar crescent visibility criterion, with a majority of the studies placing focus on the design and social aspects of it. Therefore, this article aims to provide a review on the modern lunar crescent visibility criterion, which covers the scientific outlook of a lunar crescent visibility criterion: data locality, prediction strength and weaknesses, and its long-term legacy in visibility. The said review is conducted using systematic literature analysis, and specific inclusion and exclusion criteria, performed based on 27 works on the lunar crescent visibility criterion that pass the selection criteria. The review suggests that a new outlook on modern lunar crescent visibility criterion study can be obtained, by conducting an assessment of collected database of lunar crescent sightings, and by providing a comparative analysis tool for modern lunar crescent visibility criterion.